Traces of a stream : literacy and social change among African American women - Royster, Jacqueline Jones (Pittsburgh series in composition, literacy, and culture., 2000)
"A showcase for nineteenth-century African American women, and particularly elite women, as a group of writers who are currently underrepresented in rhetorical scholarship."--Cover